Pressurized entrained-flow pyrolysis of microalgae: Enhanced production of hydrogen and nitrogen-containing compounds. (May 2018) - Maliutina, Kristina; Tahmasebi, Arash; Yu, Jianglong
Highlights: The influence of pressure on pyrolysis behavior of microalgae was investigated. Pyrolysis at elevated pressures significantly promoted the yield of H2 in bio-gas. The yields of PAHs and N-containing species increased drastically at high pressure. The carbon structure of bio-chars became more ordered at higher pressures. Pressurized pyrolysis is promising for polygeneration of H2, fine chemicals and bio-char. Abstract: Pressurized entrained-flow pyrolysis of Chlorella vulgaris microalgae was investigated. The impact of pressure on the yield and composition of pyrolysis products were studied. The results showed that the concentration of H2 in bio-gas increased sharply with increasing pyrolysis pressure, while those of CO, CO2, CH4, and C2 H6 were dramatically decreased. The concentration of H2 reached 88.01 vol% in bio-gas at 900 °C and 4 MPa. Higher pressures promoted the hydrogen transfer to bio-gas. The bio-oils derived from pressurized pyrolysis were rich in nitrogen-containing compounds and PAHs. The highest concentration of nitrogen-containing compounds in bio-oil was achieved at 800 °C and 1 MPa. Increasing pyrolysis pressure promoted the formation of nitrogen-containing compounds such as indole, quinoline, isoquinoline and phenanthridine. Higher pyrolysis pressures led to increased sphericity, enhanced swelling, and higher carbon order of bio-chars. Pressurized pyrolysis of biomass has a great potential for poly-generation of H2, nitrogen containing compounds and bio-char.